In Vitro Susceptibility to Miltefosine of Leishmania infantum (syn. L. chagasi) Isolates from Different Geographical Areas in Brazil - Caroline Ricce Espada; Erica V. de Castro Levatti; Mariana Côrtes Boité; Dorcas Lamounier; Jorge Alvar; Elisa Cupolillo; Carlos Henrique Nery Costa; Joelle Rode; Silvia R. B. Uliana (Microorganisms, 2021)
Treatment of visceral leishmaniasis in Brazil still relies on meglumine antimoniate, with less than ideal efficacy and safety, making new therapeutic tools an urgent need. The oral drug miltefosine was assayed in a phase II clinical trial in Brazil with cure rates lower than previously demonstrated in India. The present study investigated the susceptibility to miltefosine in 73 Brazilian strains of Leishmania infantum from different geographic regions, using intracellular amastigote and promastigote assays. The EC50 for miltefosine of 13 of these strains evaluated in intracellular amastigotes varied between 1.41 and 4.57 μM. The EC50 of the 73 strains determined in promastigotes varied between 5.89 and 23.7 μM. No correlation between in vitro miltefosine susceptibility and the presence of the miltefosine sensitive locus was detected among the tested strains. The relatively low heterogeneity in miltefosine susceptibility observed for the 73 strains tested in this study suggests the absence of decreased susceptibility to miltefosine in Brazilian L. infantum and does not exclude future clinical evaluation of miltefosine for VL treatment in Brazil.